PENERAPAN MODEL DISCOVERY LEARNING BERBANTU MEDIA AUDIOVISUAL UNTUK MENINGKATKAN HASIL BELAJAR PADA SISWA KELAS V TEMA 1 SDN WARU TAHUN AJARAN 2022/2023 - Dewi Indah Kurniasari (Universitas Ngudi Waluyo, 2022)
The problem that prompted the implementation of this research was the learning outcomes of fifth graders at SD Negeri Waru on daily tests only 9 out of 20 students achieved the Minimum Completeness Criteria (KKM). The subjects of this study were all fifth grade students of SD Negeri 1 Waru, namely 20 students. This type of Classroom Action Research follows the Mc Taggart model which is carried out in 3 cycles. The results of the study showed an increase in the percentage from cycle 1 then increased continuously until cycle 3. The percentage of student learning outcomes from cycle 1 showed completeness of 55% of the number of students with a classical average of 65.5 then increased in cycle 2 to 70% with a classical average of 73.5 and again increased in cycle 3 to 90% with a classical average of 82. Based on the results of the study, it was concluded that by applying the Discovery Learning learning model assisted by audiovisual media, it could improve the learning outcomes of theme 1 in the fifth grade students of SD Negeri Waru.